Screening for malignant melanoma-a critical assessment in historical perspective - Wolfgang Weyers (Mattioli1885, 2018)
Screening for melanoma has been advocated for many years because early detection and excision have been regarded as the most important measure to lower mortality from that neoplasm. In the past decade, concern has been raised by epidemiologists that screening might result in excision chiefly of "inconsequential cancer," i.e., melanomas that would never have progressed into life-threatening tumors, a phenomenon referred to by the misleading term "overdiagnosis." Without any firm evidence, that speculation has been embraced worldwide, and incipient melanomas have been trivialized. At the same time, efforts at early detection of melanoma have continued and have resulted in biopsy of pigmented lesions at a progressively earlier stage, such as lesions with a diameter of only 2, 3, or 4 mm. Those tiny lesions often lack sufficient criteria for clinical and histopathologic diagnosis, the result being true overdiagnoses, i.e., misdiagnoses of melanocytic nevi as melanoma. This is especially true if available criteria for histopathologic diagnosis are diminuished even further by incomplete excision of lesions. The reliability of histopathologic diagnosis is far higher in excisional biopsies of lesions that were given some more time to develop changes that make them recognizable. Biopsy of pigmented lesions with a diameter of 6 mm has been found to result in a far higher yield of melanomas. In addition to better clinical judgment, slight postponement of biopsies bears the promise of substantial improvement of the reliability of histopathologic diagnosis, and of alleviating true overdiagnoses.